Do measures of physical function enhance the prediction of persistent pain and disability following a whiplash injury? Protocol for a prospective observational study in Spain. Issue 10 (7th October 2020) - Alalawi, Ahmed; Luque-Suarez, Alejandro; Fernandez-Sanchez, Manuel; Gallina, Alessio; Evans, David; Falla, Deborah
Abstract : Introduction: Not all factors that predict persistent pain and disability following whiplash injury are known. In particular, few physical factors, such as changes in movement and muscle behaviour, have been investigated. The aim of this study is to identify predictive factors that are associated with the development of persistent pain and disability following a whiplash injury by combining contemporary measures of physical function together with established psychological and pain-related predictive factors. Methods and analysis: A prospective observational study will recruit 150 consecutive eligible patients experiencing whiplash-related symptoms, admitted to a private physiotherapy clinic in Spain within 15 days of their whiplash injury. Poor outcome will be measured using the Neck Disability Index (NDI), defined as an NDI score of 30% or greater at 6 months post injury. Candidate predictors, including demographic characteristics, injury characteristics, pain characteristics, self-reported psychosocial factors and physical factors, will be collected at baseline (within 15 days of inception). Regression analyses will be performed to identify factors that are associated with persistent neck pain and disability over the study period. Ethics and dissemination: The project has been approved by the Ethics Committee of the province of Malaga, Spain (#30052019). The results of this study will be published in peer-reviewed journals.